The social income of Eire, 1938-40 - Duncan, G. A. (Statistical and Social Inquiry Society of Ireland, 1941)
A paper read before the Society on Thursday, 26th October, 1939 carried the investigation up to 1937, with provisional estimates for 1938 and conjectures for 1939. Of the seven heads into which monetary income was there divided, five (fisheries, distribution, personal service, housing and income from abroad) must provisionally be taken at the figures established for 1937-38, since the limits of our additional knowledge and the scope of this present note do not admit radical revision. In the case both of agriculture and industry (accounting in 1937 for almost exactly half the total social income), where variations are more directly calculable, the continued steep upward movement of prices has necessitated an upward revision of the previous tentative figures.
Keywords: Social income; Agriculture; 314.15